STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA KARYAWAN (STUDI KASUS DI PT JAPFA COMFEED INDONESIA Tbk. POULTRY BREEDING DIVISION UNIT HATCHERY SUKAJAWA) - Karina Shinta Puspitarani; Harun Al Rasyid; Tanto Pratondo Utomo; Erdi Suroso (Jurnal Agroindustri Berkelanjutan, 2023)
PT Japfa Comfeed Indonesia Tbk. Poultry Breeding Division Hatchery Unit Sukajawa is a company that really pays attention to its human resources, but developing human resources to improve employee performance is not optimal yet, and a strategy is needed to solve these problems. This study aims to identify internal and external factors regarding human resource development in improving employee performance and to formulate human resource development strategies in improving employee performance. The research method used SWOT analysis. This study obtained the results of internal factors, which became the main strength are training for new employees and strong support from top leaders to conduct training and development (0.47), and the biggest weakness was employee discipline (0.36). The external factor that became the main opportunity was a lot of collaboration with various agencies (0.73), and the biggest threat was advances in more sophisticated technology with limited employee capabilities (0.70). Human resource development strategy in improving employee performance is appropriate with aggressive strategies such as collaborating in training new employees with field offices and various agencies, increasing training and human resource development, and recruiting competent employees. The existence of this strategy is expected to increase employee performance.